Deteksi transmisi virus dengue pada nyamuk wild Aedes Aegypti betina di Kota Manado - Trovancia, Grace; Sorisi, Angle; Tuda, Josef S.B. (e-Biomedik, 2016)
Abstract: Dengue hemorrhagic fever is an acute disease with clinical manifestations of hemorrhage caused by dengue virus infection. Manado is endemic dengue. Dengue virus has the ability to maintain its existence in nature through horizontal and vertical transmission. There are several ways to detect the dengue virus by Reverse Transcription-Polymerase Chain Reaction (RT-PCR) and immunohistochemistry Streptavidin Biotin Peroxidase Complex (ISBPC). This research aims to determine the wild Aedes aegypti population in Manado and to detect dengue virus in wild mosquito Aedes aegypti by ISBPC methods. This was a descriptive survey study with a cross sectional design to describe the transmission of dengue virus in wild mosquito Aedes aegypti in the city of Manado. The results showed that there were 5 wild Aedes aegypti mosquitoes positive for dengue virus, and 36 wild Aedes aegypti mosquitoes negative containing dengue virus. Conclusion: Of the 41 samples immunohistochemistry tested, 5 samples showed dengue virus transmission in wild mosquito Aedes aegypti in Manado which is a positive possibility of horizontal transmission.Keywords: detection of dengue virus, transmission, wild Aedes aegypti, Manado.Â Abstrak: Demam berdarah dengue adalah suatu penyakit akut dengan manifestasi klinis perdarahan yang disebabkan oleh infeksi virus dengue. Manado merupakan daerah endemis demam berdarah. Virus dengue memiliki kemampuan untuk mempertahankan keberadaannya di alam melalui transmisi horizontal dan vertikal. Ada beberapa cara untuk mendeteksi virus dengue yaitu Reverse Transcription-Polymerase Chain Reaction (RT-PCR) dan imunohistokimia Streptavidin Biotin Peroxidase Complex (SBPC). Penelitian ini bertujuan untuk mengetahui populasi nyamuk wild Aedes aegypti di Kota Manado dan mendeteksi virus dengue pada nyamuk wild Aedes aegypti dewasa menggunakan metode imunohistokimia streptavidin biotin peroxidase complex (ISBPC). Jenis penelitian ialah survei deskriptif dengan desain potong lintang untuk mengetahui gambaran transmisi virus dengue pada nyamuk wild Aedes aegypti betina di Kota Manado. Hasil pene;itian mendapatkan 5 nyamuk wild Aedes aegypti positif mengandung virus dengue, dan 36 nyamuk wild Aedes aegypti negatif mengandung virus dengue. Simpulan: Berdasarkan hasil penelitian dapat disimpulkan bahwa dari 41 sampel yang telah diuji imunohistokimia, 5 sampel gambaran transmisi virus dengue pada nyamuk wild Aedes aegypti betina di Kota Manado yang kemungkinan transmisi horizontal adalah positif. Kata kunci: deteksi virus dengue, transmisi, wild Aedes aegypti, Manado.